The Association Between Plant-Based Diet Indices and Obesity and Metabolic Diseases in Chinese Adults: Longitudinal Analyses From the China Health and Nutrition Survey - Chen, Bo; Zeng, Jingjing; Qin, Minghui; Xu, Wenlei; Zhang, Zhaoxia; Li, Xiaying; Xu, Shaoyong (Frontiers in Nutrition, 2022)
Background: A wide range of health benefits are associated with consuming a diet high in plant-based foods. Diet quality can be accurately assessed using plant-based diet indices, however there is inadequate evidence that plant-based diet indices are linked to obesity, hypertension, and type 2 diabetes(T2D), especially in Chinese cultures who have traditionally consumed plant-rich foods. Methods: The data came from the China Nutrition and Health Survey. Overall, 11,580 adult participants were enrolled between 2004 and 2006 and followed up until 2009 or 2015 (follow-up rate: 73.4%). Dietary intake was assessed across three 24-hour recalls, and two plant-based dietary indices (overall plant-based diet indice (PDI) and healthy plant-based diet indice (hPDI)) were calculated using China Food Composition Code and categorized into quintiles. The study's endpoints were overweight/obesity, hypertension, and T2D. The Hazard ratio (HR) and dose-response relationship were assessed using the Cox proportional risk model and restricted cubic splines. Results: During the median follow-up period of more than ten years, 1270 (33.4%), 1509 (31.6%), and 720 (11.5%) participants developed overweight / obesity, hypertension, and T2D, respectively. The higher PDI score was linked with a reduced risk of overweight/obesity [HR: 0.71 (95% CI: 0.55-0.93), P-trend <0.001], hypertension [HR: 0.63 (95% CI: 0.51-0.79), P-trend <0.001], and T2D [HR: 0.79 (95% CI: 0.72-0.87), P-trend <0.001]. The hPDI score was inversely associated with overweight/obesity [HR: 0.79 (95% CI: 0.62- 0.98), P-trend = 0.02] and T2D [HR: 0.84 (95% CI: 0.75-0.93), P-trend = 0.001]. In the aged <55-year-old group, subgroup analysis indicated a significant negative association between PDI/hPDI and overweight/obesity, hypertension, and T2D. Conclusion: The PDI and hPDI scores were very similar in application in Chinese populations, and our findings highlight that adherence to overall plant-based diet index helps to reduce the risk of T2D, obesity, and hypertension in Chinese adults who habitually consume plant-based foods, especially for those aged <55 year. Further understanding of how plant-based diet quality is associated with chronic disease will be needed in the future, which will help develop dietary strategies to prevent diabetes, hypertension, and related chronic diseases.